2003
DOI: 10.1086/376457
|View full text |Cite
|
Sign up to set email alerts
|

Prematurity Is the Major Risk Factor for Late‐Onset Group B Streptococcus Disease

Abstract: A case-control study was conducted in the greater Houston area to determine risk factors for late-onset group B streptococcus (GBS) disease (onset of disease or first positive culture between 7 and 180 days after birth). Characteristics of 122 case patients diagnosed during 1995-2000 were compared with control subjects matched for birth hospital and date of birth. Half the case patients were preterm infants, 84% of whom were born at <34 weeks of gestation. The risk for late-onset GBS disease increased by a fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
2
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(96 citation statements)
references
References 35 publications
6
84
2
4
Order By: Relevance
“…This confirms that preterm delivery is the most important perinatal risk factor in late onset disease. 28 Most of the patients with very early onset GBS sepsis and very early onset probable GBS sepsis were born in hospital (85% and 87%, respectively) in contrast with about 70% of all deliveries in the Netherlands. This may be explained by the fact that in the Netherlands, pregnant women with risk factors are usually referred to hospital.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms that preterm delivery is the most important perinatal risk factor in late onset disease. 28 Most of the patients with very early onset GBS sepsis and very early onset probable GBS sepsis were born in hospital (85% and 87%, respectively) in contrast with about 70% of all deliveries in the Netherlands. This may be explained by the fact that in the Netherlands, pregnant women with risk factors are usually referred to hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to term infants, preterm infants are much more susceptible to invasive GBS disease, in particular LONS and VLONS. In a recent case-control study of 122 infants with GBS LONS, 84% of patients were born at Ͻ34 weeks of gestation, and the risk for GBS LONS increased by a factor of 1.34 (95% CI, 1.15 to 1.56) for each week of decreasing gestation (290). This is probably due in part to low levels of maternal antibodies, which cross the placenta in the third trimester of pregnancy.…”
Section: Gram-positive Organismsmentioning
confidence: 99%
“…16 Colonisation of the mother is less predictive for late-onset GBS infection, with prematurity the major risk factor. 17 The association between the rates of maternal colonisation, transmission and infection has been established. A meta-analysis 12 of six studies of the maternal and baby colonisation rates in an untreated general population showed a transmission rate of 36.4% (95% CI 28.1-45.0%).…”
Section: Transmissionmentioning
confidence: 99%